2020
DOI: 10.1002/ep.13479
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐light‐driven photocatalytic activity of kaolinite: Sensitized by in situ growth of Cu‐TiO2

Abstract: Sensitized kaolinite with improved visible‐light catalytic activity was prepared via a facile in‐situ growth of nanosized Cu‐TiO2 on the surface of the sulfated kaolinite impregnated in Cu‐TiO2 sol. The as‐prepared photocatalysts were characterized in terms of various techniques. The transmission electron microscope and energy dispersive spectrometer results revealed that Cu‐TiO2 could grow on the surface of the pretreated kaolinite and the aggregation of Cu‐TiO2 was successfully inhibited. The X‐ray photoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The obtained results are shown in figure 4 The nitrogen adsorption-desorption isotherm and the pore size distribution of the 10CZK sample is shown in figure 6. The plot of the 10CZK sample as it is indicated in figure 6(a) corresponds to type IV in which it has mesoporous characteristics [68]. It is also indicated that the hysteresis is a H3-type and the pore channels are mainly mesopores [68].…”
Section: Sem and Tem Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…The obtained results are shown in figure 4 The nitrogen adsorption-desorption isotherm and the pore size distribution of the 10CZK sample is shown in figure 6. The plot of the 10CZK sample as it is indicated in figure 6(a) corresponds to type IV in which it has mesoporous characteristics [68]. It is also indicated that the hysteresis is a H3-type and the pore channels are mainly mesopores [68].…”
Section: Sem and Tem Analysismentioning
confidence: 93%
“…The plot of the 10CZK sample as it is indicated in figure 6(a) corresponds to type IV in which it has mesoporous characteristics [68]. It is also indicated that the hysteresis is a H3-type and the pore channels are mainly mesopores [68]. On the other hand, A H3-type hysteresis loop showed the presence of narrow slit-like pore particles with internal voids of irregular shape and broad size distribution as a result of the composite catalyst [69].…”
Section: Sem and Tem Analysismentioning
confidence: 94%
“…Lipid peroxidation and oxidative stress lead to increased membrane permeability [222]. Furthermore, some kaolin minerals have photocatalytic properties [223,224] and may induce photodegradative damage to bacteria. Finally, an altered pH and oxidation state of the microenvironment can hamper bacteria [225,226] and further result in the combined action of Al and Fe on membranes and on intracellular proteins [203,227].…”
Section: (B) Loam Clay and Other Soil Minerals In Pharmaceuticals And Cosmeticsmentioning
confidence: 99%